The Association Between Gait Speed and Sleep Problems Among Chinese Adults Aged 50 and Greater - Wang, Lili; Zou, Benxu (Frontiers in Neuroscience, 2022)
Objective The relationship between sleep problems and walking speed has been less explored. The present cross-sectional study was to investigate the association between sleep quality and sleep duration and gait speed in Chinese adults. Methods A total of 13,367 participants were recruited in this cross-sectional study, retrieving the data from the Global Aging and Adult Health Survey (SAGE). Gait speed was measured using the 4-m walking test. Age, sex, education years, smoking status, alcohol consumption, physical activity, chronic disease, sleep problems were self-reported by participants. To explore the association between sleep problems and gait speed, multivariate linear regression models were employed. Results In the adjusted model, poor sleep quality and longer sleep duration were significantly associated with slower normal walking speed in Chinese adults (p < 0.001). Moreover, there were negatively significant associations between normal gait speed and sleep quality in male adults (p < 0.01). Conclusion The findings suggest that slower normal walking speed was associated with poor sleep quality and longer sleep duration (>8 h) in Chinese male adults.